2016
DOI: 10.7150/jca.17162
|View full text |Cite
|
Sign up to set email alerts
|

Positive Prehabilitative Effect of Intense Treadmill Exercise for Ameliorating Cancer Cachexia Symptoms in a Mouse Model

Abstract: Due to the importance of exercise in prehabilitation, we conducted this study to understand the effects of different exercise intensities on cancer-related cachexia.Forty adult male CDF1 mice were randomly divided into a non-cancer control group (N=10, NC), cancer control group (N=10, CC), cancer with moderate exercise group (N=10, ME, 70% maxHR), and cancer with intense exercise group (N=10, SE, 90% maxHR) for obtaining data such as tissue weight and body weight changes, quality of life (QoL) indicators, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 22 publications
(29 reference statements)
3
30
0
Order By: Relevance
“…Similarly, in a phase II trial, aerobic ET (220 min/week for 12 weeks) after treatment for breast or colorectal cancer reduced the circulating levels of IL-6 with no additive effect of the anti-diabetic drug metformin in patients [ 237 ]. In rodent cancer models, aerobic ET has also been shown to decrease plasma IL-6 concentrations [ 238 ] and the cytokine content of adipose tissue [ 63 ]. Thus, ET is likely to treat chronic inflammation in patients as well as cancer survivors but whether this would impinge on metabolic function is unknown.…”
Section: Exercise Is the Most Powerful Means To Improve Metabolic mentioning
confidence: 99%
“…Similarly, in a phase II trial, aerobic ET (220 min/week for 12 weeks) after treatment for breast or colorectal cancer reduced the circulating levels of IL-6 with no additive effect of the anti-diabetic drug metformin in patients [ 237 ]. In rodent cancer models, aerobic ET has also been shown to decrease plasma IL-6 concentrations [ 238 ] and the cytokine content of adipose tissue [ 63 ]. Thus, ET is likely to treat chronic inflammation in patients as well as cancer survivors but whether this would impinge on metabolic function is unknown.…”
Section: Exercise Is the Most Powerful Means To Improve Metabolic mentioning
confidence: 99%
“…As suggested in the context of preclinical studies, aerobic and strength training seem to induce a relevant benefit against cancer cachexia [87,88]. To our knowledge, only one study is available in patients with cachexia.…”
Section: Strength and Muscle Massmentioning
confidence: 99%
“…To possibly conquer cancer or at least ameliorate the symptoms of cancer, convergent insights from multidisciplinary aspects of cancer-related studies are indispensable. In vivo and in vitro (Jee et al, 2016) results from direct and practical experiments have been important; furthermore, big data analysis can be added as an allied aid. A study introduced a synergistic double-check of the interrelationship of cancer-regulating genes in colorectal cancer from precedent published datasets to build target gene DBs based on data mining from the IluminaGA_miRNASeq platform served by The Cancer Genome Atlas (https://cancergenome.nih.gov/) by validating in vitro experiments.…”
Section: Big Data Analysis To Identify Parameters Related To Colorectmentioning
confidence: 99%
“…These results suggest that designing tailor-made ideal exercise programs using the analyzed parameters in this study is one way to prevent or alleviate the symptoms of colorectal cancer, although the exercise-related parameter in this study did not indicate details such as the intensity or duration of exercise because these factors appear to be more important to obtain the maximal effect of exercise intervention. Jee et al (2016) reported that high rather than moderate intensity of exercise confers a greater effect on various parameters of cancer models. To design an individual exercise program, adjusting for the markers found to be significant, such as SEX, BMI, BP_LWST, BLDS, HMG, SGPT_ALT, and WAIST, to specify an idealistic exercise program should be developed to prevent colorectal cancer.…”
Section: Individualized Exercise Interventions To Reduce the Incidencmentioning
confidence: 99%